Exploring the role of an IBT-based Informal teaching practice at an edutainment centre on pre-service English language teachers - Karacan, Cemil Gökhan; Kesen Mutlu, Aynur (Springer, 2023)
The field experience in teacher education programs is limited to the formal teaching at assigned schools. However, there is a need for opportunities for pre-service teachers to practice teaching in other learning contexts. This multiple instrumental case study explored the role of an Inquiry-based Teaching-based informal teaching practice at an edutainment center on a group of 23 pre-service English language teachers. The data were collected through one-on-one semi-structured interviews, retrospective reflection papers and focus group interview. Findings showed that pre-service English language teachers gained valuable insights into different ways of managing the classroom and sustaining interaction with children. Furthermore, they increased their teacher awareness and became more autonomous teachers. The findings of this study have implications for teacher education program designers and teacher educators seeking to enhance the field experience of pre-service teachers.
Keywords: Edutainment Center; Informal Teaching Practice; Inquiry-Based Teaching; Pre-Service English Language Teachers